What is the relationship between risk management and the specific needs of SMEs? - EL MOUDDEN , Maryam; BALHADJ , Said (Revue Internationale des Sciences de Gestion, 2024)
Today, Moroccan SMEs, like all businesses, are faced with risks (financial, economic, environmental, etc.) that affect their survival, reputation and environment. It is for this reason that the SME must evolve its organizational system and master and practice these risks, which are currently necessary for its good management. Indeed, one of the characteristics of an SME is that it is highly personalized and linked to the owner-manager as the key figure in the organization, who is employed to make decisions and guide the company through uncertain situations that are fraught with risk at all levels. The strong message underlined in this article is to explore a review of the professional literature on risk management for SMEs in Morocco, and to understand whether today’s SMEs have sufficient structural, organizational and managerial capabilities to manage their risks?